Effect of Chemical Degradation of Sodium Alginate on Capsaicin Encapsulation - Dominika Kulig; Łukasz Bobak; Andrzej Jarmoluk; Aleksandra Szmaja; Żaneta Król-Kilińska; Anna Zimoch-Korzycka (Molecules, 2023)
Capsaicin is known as an oily extract of paprika that is characterized by pungent taste and bioactivity. It also may cause irritation to the mouth and stomach which is why is so important to immobilize capsaicin on a carrier to prevent it. The usage of alginate oligomers, which has an antioxidant potential compared to alginate, is of benefit because it may be used in the immobilization of bioactive substances that are fragile to oxidation. The purpose of this study was to use sodium alginate oligomers as a coating material in the encapsulation process of paprika oleoresin. Alginate oligomers were produced by chemical degradation with hydrogen peroxide. The characteristics of the samples were obtained by measuring the viscosity, the contact angle of the surface, and the surface tension of solutions. The obtained solution of alginate oligomers served as the carrier material for the immobilization of capsaicin. Capsules were prepared by ionic gelation using a calcium chloride solution as a crosslinking agent. In this way, capsules without and with the core (capsaicin) were prepared and their ability to scavenge free radicals (DPPH) and iron-reducing properties (FRAP) were determined. The stability of the capsules was examined by thermal decomposition and under conditions of the gastric and small intestine, and capsaicin content was detected using high-performance liquid chromatography. It was found that alginate oligomers could be used in the encapsulation of bioactive compounds and the efficiency was above 80%. Capsule production from alginate oligomers affected their thermal stability. The use of alginate derivatives as a carrier increased the antioxidant properties of the finished product, as well as its ability to reduce iron ions. The use of alginate oligomers as a coating material prevented the active substance from being released too early in the conditions of the small intestine, prolonged the stability of the capsules, and supported their durability in gastric conditions.